Solusi Al-Qur’an terhadap Musykilat Al-Iqtisadiyyah: Kajian Tafsir Surah Al-Isra’ - Nadia, Nadia; Tarigan, Azhari Akmal; Syahreza, Rahmi (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
This study aims to analyze the solutions offered by the Qur'an to the musykilat al-iqtisadiyyah in the context of modern economics, by examining the interpretation of Surah Al-Isra' verses 16, 26, and 29. The background of this study focuses on the widening inequality of wealth distribution and social injustice in society, as well as its impact on social and economic stability. The research method used is a descriptive qualitative approach with a library research type. The results of this study reveal that the Qur'an provides solutions in the form of fair wealth management, wealth distribution through zakat, alms, and social assistance, as well as avoiding stinginess and wastefulness. The findings of this study indicate that the solutions offered by the Qur'an are very relevant to reducing social inequality, improving the wealth distribution system, and creating a more inclusive and sustainable economy. This study contributes to the development of Islamic economic thought in facing the challenges of the modern economy, by emphasizing the importance of the principles of justice, balance, and social responsibility in the management of economic resources.